Effects of climate, soil and water source on determining exchangeable copper concentration in lowland paddy fields in Sri Lanka - Charuka Chandrasekara; Mojith Ariyaratne; Ranga Madushan; Upul Rathnayake; Rohana Thilakasiri; Harsha Kadupitiya; Rohana Chandrajith; Chalinda Beneragama; Lalith Suriyagoda (Circular Agricultural Systems)
Copper (Cu) is an essential micronutrient for rice. However, the current status of Cu in Sri Lankan paddy soils is not known. Therefore, the current study was conducted to determine the distribution of exchangeable Cu concentration and examine the interactive effects of the agro-climatic zone (ACZ), soil order, and water source in determining the exchangeable Cu concentration in lowland paddy fields in Sri Lanka. A total of 7,544 soil samples representing six ACZs, six soil orders, and three water sources were collected using a stratified random sampling approach. Soil exchangeable Cu fraction was extracted in 0.01 M CaCl2 and measured using Inductively Coupled Plasma Mass Spectrophotometry. Exchangeable Cu concentration was in the range of 0.04−728 µg·kg−1 with a mean value of 62.4 µg·kg−1. Only 5% of the soil samples tested had Cu concentration greater than 200 µg·kg−1 indicating a widespread Cu deficiency in Sri Lankan paddy fields (i.e. critical level causing Cu deficiency; 200–300 µg·kg−1). Among the climatic zones Wet zone had higher and the Dry zone had lower Cu concentrations. Among the soil orders, histosols had higher and alfisols had lower Cu concentrations. Water sources used for rice cultivation did not determine Cu concentration. Moreover, Cu concentration was positively correlated with soil pH. As most of the soil samples were deficient in soil exchangeable Cu, spatial maps generated in the current work could be used to develop ACZ and soil order-specific agronomic and management strategies to improve soil Cu fertility status.